High-weather-resistance warning sign material for ship deck and preparation method of high-weather-resistance warning sign material

By using high weather resistance warning marking materials with aluminum foil and polyester adhesive layers on the ship deck, the problem of insufficient weather resistance in the marine environment is solved, and the long-term clear and stable material, excellent anti-slip and night visibility of the material are achieved, and the safety and reliability of the ship are improved.

CN119662141APending Publication Date: 2025-03-21SHANGHAI HANKER PLASTICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411550574.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The warning sign materials on existing ship decks are difficult to maintain long-term clearness and stability in marine environments, and the anti-slip performance and night visibility are insufficient, resulting in safety hazards and potential accident risks.

Method used

The polyester glue layer between the aluminum foil layer and the bottom layer is used. The polyester glue layer is composed of high-performance materials such as acrylate resin, ethyl acetate, and encapsulated rare earths. By finely controlling the solid content and viscosity of the resin, as well as the feeding ratio of the monomer raw materials, the material is ensured with excellent weather resistance, anti-slip performance and luminous performance.

Benefits of technology

It achieves high weather resistance that maintains bright colors and is not easy to fade or age in the marine environment for a long time, improves anti-slip performance and night visibility, enhances the safety marking effect on the ship deck, reduces the risk of accidents, and ensures the safety of crew members and cargo.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a high-weather-resistance warning marking material for a ship deck and a preparation method thereof.The marking material comprises an aluminum foil layer and a bottom layer, the aluminum foil layer and the bottom layer are bonded through a polyester adhesive layer, and the polyester adhesive layer is prepared from acrylate resin, ethyl acetate, wrapping rare earth, a flame retardant, a flatting agent, an anti-aging agent and a mineral oil defoaming agent; the acrylate resin is prepared from an acrylic monomer, a vinyl triethoxy silane monomer and glycidyl methacrylate; the preparation method of the identification material comprises the steps of preparation and assembly of the polyester adhesive. According to the warning mark material, the polyester adhesive layer with a special proportion is adopted and comprises various materials such as acrylate resin and wrapping rare earth, so that the whole marking material has excellent weather resistance, the color can be kept bright for a long time even in a severe marine environment, fading or aging is not likely to happen, and the service life of the marking material is prolonged. And the anti-skid performance and the long afterglow time are achieved, and therefore the safety sign effect on the ship deck is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of marking materials, and in particular to a highly weather-resistant warning marking material for ship decks and a preparation method thereof. Background Art

[0002] With the booming global shipping industry, the issue of ship safety has risen to an unprecedented level. Deploying warning sign materials with excellent weather resistance on the key area of ​​the ship, the deck, is not only an important measure to improve navigation safety, but also a solid line of defense to effectively prevent potential accident risks and ensure the safety of crew members and cargo.

[0003] Given that ship decks are exposed to the harsh and changeable marine environment for a long time, they are subject to multiple challenges such as salt spray erosion, moisture infiltration and strong ultraviolet radiation. These extreme conditions pose a severe test to the warning sign materials on the deck, requiring them to have high weather resistance to resist environmental erosion.

[0004] Many warning sign materials on the market today are unable to cope with the harsh challenges of the marine environment. They often fade quickly and suffer from severe wear and tear, which makes the sign information blurred and difficult to discern, thereby weakening its proper warning effect. In addition, the deficiencies of these materials in terms of anti-slip performance and afterglow time (i.e. visibility at night or in low light environments) have exacerbated safety hazards and posed a potential threat to the safe operation of ships.

[0005] Therefore, the development and application of a highly weather-resistant warning sign material that can remain clear and stable for a long time in the marine environment and has excellent anti-slip and night visibility has become a key issue that needs to be urgently addressed in the field of ship safety. Summary of the invention

[0006] To solve the above problems, the present application provides a highly weather-resistant warning sign material for ship decks and a preparation method thereof, aiming to enable the prepared warning sign material to effectively cope with extreme conditions such as salt spray erosion, moisture infiltration and strong ultraviolet radiation in the marine environment, while improving the anti-slip performance and visibility at night or in low-light environments, thereby comprehensively enhancing the safety and reliability of ship navigation.

[0007] In the first aspect, the present application provides a highly weather-resistant warning sign material for ship decks using the following technical solution: A highly weather-resistant warning sign material for ship decks, comprising an aluminum foil layer and a bottom layer, wherein the aluminum foil layer is composed of forged aluminum foil, and the bottom layer is composed of environmentally friendly isolation paper; the aluminum foil layer and the bottom layer are bonded by a polyester adhesive layer, wherein the raw materials for preparing the polyester adhesive layer, by weight percentage, include: Acrylate resin 28-30% Ethyl acetate 44-48% Encapsulated rare earth 10-15% Flame retardant 3-4% Leveling agent 1-3% Anti-aging agent 1-3% Mineral oil defoamer 1-2% Wherein, the acrylate resin is prepared from acrylic acid monomer, vinyl triethoxysilane monomer and glycidyl methacrylate, and its specific preparation method includes: S1, uniformly mix acrylic acid monomer and vinyl triethoxysilane monomer, place them in a reaction container, add solvent and initiator, raise the temperature to 75-105° C. and keep the temperature for reaction for 1-1.5 hours to obtain mixture A; S2. Add glycidyl methacrylate to the mixture A after the reaction in S1, then raise the temperature to 140-155° C. and keep the mixture to react for 2.5-3 hours, and then obtain the acrylic resin after post-treatment.

[0008] By adopting the above technical solution: the highly weather-resistant warning sign material has excellent weather resistance and night visibility, which comprehensively improves the safety sign effect on the ship deck. These performance improvements directly enhance the safety and reliability of ship navigation, effectively prevent potential accident risks, and ensure the safety of crew members and cargo.

[0009] Analyzing the reasons, it may be: The aluminum foil layer is made of forged aluminum foil, which has good corrosion resistance and durability, and can effectively resist salt spray erosion and moisture infiltration in the marine environment. The special formula in the polyester adhesive layer, including acrylate resin, ethyl acetate, encapsulated rare earth and other ingredients, work together to enhance the weather resistance of the material. In particular, in the preparation process of acrylate resin, by introducing vinyl triethoxysilane monomer and glycidyl methacrylate, the resin structure is made more stable, which can effectively resist strong ultraviolet radiation and prevent material aging, fading and deformation; Encapsulated rare earth materials are introduced into the polyester adhesive layer due to their unique luminescent properties. These rare earth elements can emit bright and lasting light after being stimulated by ultraviolet light, visible light or other forms. This luminescent property not only enhances the visibility of warning signs during the day, but more importantly, it provides additional lighting effects at night or in low-light environments, making the warning information more eye-catching, thereby greatly reducing the risk of accidents.

[0010] Preferably, the acrylic resin has a solid content of 52-55% and a viscosity of 1250-2500 mPa·s.

[0011] By adopting the above technical solution: optimizing the solid content and viscosity of the acrylic resin, the coating quality, construction performance, coating performance and compatibility with other components of the high weather-resistant warning sign material for ship decks can be significantly improved, providing a more reliable guarantee for ship navigation safety.

[0012] Preferably, in the preparation step of the acrylic resin, the feeding amounts of acrylic acid monomer, vinyl triethoxysilane monomer and glycidyl methacrylate are calculated by weight ratio of acrylic acid:vinyl triethoxysilane:glycidyl methacrylate to be 1:(0.04-0.06):(0.01-0.02).

[0013] Preferably, in the preparation step of the acrylic resin, the feeding amounts of acrylic acid monomer, vinyl triethoxysilane monomer and glycidyl methacrylate are calculated by weight ratio of acrylic acid:vinyl triethoxysilane:glycidyl methacrylate to be 1:(0.044-0.051):(0.014-0.018).

[0014] By adopting the above technical solution: finely regulating the feeding amount ratio of each monomer raw material, the molecular weight distribution and crosslinking degree of the acrylic resin can be accurately controlled, which has a significant impact on its processing performance. The appropriate crosslinking density and molecular weight distribution give the resin more excellent fluidity and molding ability during processing, effectively reducing bubbles and defects in the processing process, and ensuring the stability of product quality; In addition, the specific monomer ratio ensures that the resin can form a tight and stable network structure after curing. This structural characteristic greatly improves the hardness, toughness and wear resistance of the resin, which is crucial for warning signs on ship decks because they need to withstand various mechanical stresses such as pedestrian trampling and cargo handling.

[0015] What is more worth mentioning is that while ensuring the high performance of the material, optimizing the feed ratio can also reasonably reduce the use of high-cost monomers, thereby effectively reducing the overall material production cost without affecting the material quality, thereby improving the product's economy and market competitiveness.

[0016] Preferably, the encapsulated rare earth is prepared by dispersing a rare earth europium complex through a sol-gel method and embedding the complex into an encapsulating matrix.

[0017] By adopting the above technical solution: the rare earth europium complex can be accurately and evenly dispersed and firmly embedded into the encapsulating matrix. This process effectively isolates the rare earth elements from direct contact with the external environment, thereby greatly improving their chemical stability and thermal stability. This stability is the cornerstone for maintaining the unique luminescence properties and other important properties of the rare earth europium complex, and is crucial to ensuring that the material can still maintain excellent performance in a complex environment.

[0018] Preferably, the rare earth europium complex is Eu(DBM)3Phen, Eu(TTA)3Bipy, Eu(TTA)3phen or Tb(TTA)3Bipy.

[0019] By adopting the above technical solution: these rare earth europium complexes usually have high chemical stability, can resist the corrosion of chemical substances such as acids and alkalis, and can also resist thermal decomposition and photodegradation to a certain extent. This stability enables them to maintain excellent luminescence properties under harsh environmental conditions.

[0020] Preferably, the encapsulating matrix is ​​a composite matrix composed of aluminum oxide and polyacrylic acid.

[0021] By adopting the above technical solution: polyacrylic acid is a high-performance organic polymer material, and its remarkable characteristics are excellent flexibility and good processing performance. These characteristics enable polyacrylic acid to be used as an important component of the composite matrix, giving the overall structure the necessary elasticity and plasticity, ensuring that the matrix can maintain a stable shape when subjected to external stress. At the same time, the addition of aluminum oxide plays a key role. It significantly enhances the mechanical strength of the matrix with its excellent hardness and wear resistance, so that the composite matrix has excellent deformation resistance and wear resistance while maintaining flexibility, achieving a perfect balance between rigidity and flexibility; Furthermore, the optical properties of aluminum oxide also bring significant advantages to the composite matrix. It has good light transmittance and its refractive index is highly matched with the rare earth europium complex. This matching effectively reduces the scattering and reflection of light inside the matrix, ensuring that light can pass through the matrix smoothly and stimulate the luminescence effect of the rare earth europium complex. Polyacrylic acid may have a positive impact on the propagation path and efficiency of light through its unique molecular structure and optical properties, further promoting the optimization of the luminescence performance of the rare earth europium complex. The synergistic effect of the two may not only improve the luminescence efficiency, but also improve the purity and saturation of the luminescent color, so that the rare earth europium complex in the composite matrix can show a brighter, more vivid and more lasting luminescence effect.

[0022] In the second aspect, the present application provides a method for preparing a highly weather-resistant warning sign material for a ship deck using the following technical solution: A method for preparing a highly weather-resistant warning marking material for a ship deck comprises the following steps: A1. Preparation of polyester glue: Add acrylate resin, then add ethyl acetate, encapsulated rare earth, flame retardant, leveling agent, antioxidant and mineral oil defoamer in a reaction vessel, raise the temperature to 95-110° C., keep the temperature for reaction for 2.5-3 hours, and obtain polyester glue; A2. Assembly: Prepare forged aluminum foil and environmentally friendly isolation paper, then coat the surface of the forged aluminum foil with the polyester glue prepared by A1 after surface pretreatment, with a coating thickness of 5-6U, and then attach the environmentally friendly isolation paper, and after curing, form an aluminum foil layer and a bottom layer to obtain a highly weather-resistant warning sign material for ship decks.

[0023] By adopting the above technical scheme: a highly weather-resistant warning sign material for ship decks with excellent performance can be produced. The material not only has high weather resistance, can maintain bright colors for a long time in the marine environment, is not easy to fade or age, but also has the characteristics of long afterglow time, anti-slip, and wear resistance, which effectively improves the safety and service life of the ship deck.

[0024] In summary, the present application includes at least one of the following beneficial technical effects: 1. The warning sign material adopts a polyester adhesive layer with a special ratio, which contains a variety of high-performance materials such as acrylic resin, ethyl acetate, and encapsulated rare earth. The overall material has excellent weather resistance. Even in harsh marine environments, it can keep bright colors for a long time and is not easy to fade or age, thereby improving the safety sign effect on the ship deck. This high weather resistance directly enhances the safety and reliability of ship navigation, effectively prevents potential accident risks, and ensures the safety of crew members and cargo; 2. The introduction of encapsulated rare earths, especially the use of rare earth europium complexes such as Eu(DBM)3Phen and Eu(TTA)3Bipy, which are uniformly dispersed and embedded in a composite matrix composed of alumina and polyacrylic acid through a sol-gel method, not only improves the chemical and thermal stability of rare earth elements, but also significantly optimizes their luminescence performance. This design enables the warning sign material to maintain a bright and vivid luminescence effect at night or in low light environments, greatly enhancing nighttime visibility and further improving the safety of ship navigation; 3. The careful preparation process of acrylic resin, including the control of solid content, viscosity and the proportion of monomer raw materials, ensures that the resin has excellent fluidity and molding ability during processing, which not only reduces bubbles and defects in the processing, but also improves the uniformity and adhesion of the coating. At the same time, leveling agent and mineral oil defoamer are added in the preparation of polyester adhesive layer to further improve the surface quality of the coating. With the combined effect of these measures, the final warning sign material has excellent coating quality and construction performance, ensuring the stability and reliability of product quality; DETAILED DESCRIPTION

[0025] The present application is further described in detail below in conjunction with the examples. Except for the special instructions below, the raw materials used in the present application are all common commercially available materials.

[0026]

[0027] Preparation Example 1-3 An acrylic resin, various raw materials and corresponding amounts (kg) are shown in the following table.

[0028]

[0029] The preparation method of the above-mentioned acrylate resin comprises the following steps: S1. In a clean and dry reaction container, acrylic acid monomer and vinyl triethoxysilane monomer are uniformly mixed in the above proportions, stirred to ensure uniform mixing, then ethyl acetate and azobisisobutyronitrile accounting for 1 wt % of acrylic acid are added to the reaction container, and the temperature is slowly raised to between 75-105° C., and the temperature is maintained for insulation reaction for 1-1.5 hours to obtain a mixture A of acrylic acid prepolymer containing silane functional groups; S2. Add glycidyl methacrylate to the mixture A obtained in S1, ensuring that it is evenly dispersed in the mixture A, further increase the reaction temperature to between 140-155° C., maintain the temperature for insulation reaction for 2.5-3 hours, and after the reaction is completed, cool, filter or centrifuge the reaction mixture to remove unreacted monomers, solvents and possible impurities, thereby obtaining an acrylate resin product.

[0030] The acrylate resin prepared in the present application has a solid content of 52% and a viscosity of 1400 mPa·s.

[0031] Preparation Example 4-7 An acrylic resin, which is different from Preparation Example 1 in that the raw material components and their corresponding weights are shown in the following table (kg).

[0032]

[0033] The preparation method of the above acrylate resin is the same as that of Preparation Example 1. Example

[0034] A highly weather-resistant warning sign material for ship decks, comprising an aluminum foil layer and a bottom layer, wherein the aluminum foil layer is made of forged aluminum foil and the bottom layer is made of environmentally friendly isolation paper; the aluminum foil layer and the bottom layer are bonded by a polyester adhesive layer; The raw materials used to prepare the above polyester adhesive layer and their corresponding weights (kg) are shown in the following table.

[0035]

[0036] The method for preparing the above-mentioned highly weather-resistant warning marking material for ship decks comprises the following steps: A1. Add the acrylic resin prepared in Preparation Example 1 to the reaction vessel, turn on the stirrer and stir at 450 rpm, add ethyl acetate as solvent in sequence, slowly add encapsulated rare earth, silver ion flame retardant, leveling agent, antioxidant and mineral defoaming oil, and stir well after each addition to ensure uniform mixing; heat to 95-110°C and maintain this temperature for insulation reaction for 2.5-3 hours. During this process, the components will undergo complex chemical reactions to form polyester glue with specific properties; A2. Select environmentally friendly isolation paper and forged aluminum foil with moderate thickness and smooth surface. Clean and degrease the forged aluminum foil to ensure that its surface is clean and free of impurities, and then perform roughening treatment. Use a coating machine to evenly coat the polyester glue prepared in A1 on the surface of the pretreated forged aluminum foil. Control the coating thickness to 5-6U. Then, before the polyester glue is completely cured, quickly and evenly attach the environmentally friendly isolation paper to the glue-coated surface. Press gently to ensure that the isolation paper and the polyester glue fit tightly to avoid bubbles or wrinkles. Finally, after curing, you have it.

[0037] In the embodiment of the present application, the encapsulated rare earth is prepared by dispersing Eu(TTA)3Bipy through a sol-gel method and embedding it into a composite matrix composed of aluminum oxide and polyacrylic acid. The specific preparation process includes: Preparation of sol: Dissolve aluminum alkoxide in ethanol to form a uniform solution. Under stirring conditions, slowly add water to initiate hydrolysis and condensation reactions to generate aluminum oxide sol. Dissolve Eu(TTA)3Bipy in a small amount of ethylene glycol and add it to the sol to ensure uniform dispersion.

[0038] Introduction of polyacrylic acid: slowly add the polyacrylic acid solution into the above sol while continuously stirring to fully mix the polyacrylic acid and the sol. The addition of polyacrylic acid may affect the viscosity and stability of the sol, so the addition speed and amount need to be controlled.

[0039] Aging and gelation of sol: Place the mixed sol in a sealed container and age it at 33°C for 18 hours to allow the particles in the sol to further polymerize and form a gel. During the aging process, pay attention to the changes in the state of the sol to prevent precipitation or over-drying.

[0040] Drying and heat treatment: The gel is vacuum dried to remove the solvent and moisture, and the dried gel is further heat treated to enhance its stability and performance.

[0041] Embodiment 2-5 A highly weather-resistant warning sign material for ship decks, which is different from Example 1 in that the polyester adhesive layer, its preparation raw materials and corresponding weights (kg) are shown in the following table.

[0042]

[0043] Embodiment 6-11 A highly weather-resistant warning sign material for ship decks, which is different from Example 1 in that the raw material acrylic resin in the polyester adhesive layer is prepared by the preparation example in the following table.

[0044] Example

[0045] A highly weather-resistant warning sign material for ship decks, which differs from Example 1 in that the raw material encapsulated rare earth in the polyester adhesive layer is prepared by dispersing Eu(TTA)3Bipy through a sol-gel method and embedding it into a composite matrix composed of zinc oxide and polyacrylic acid. Example

[0046] A highly weather-resistant warning sign material for ship decks, which differs from Example 1 in that the raw material encapsulated rare earth in the polyester adhesive layer is prepared by dispersing Eu(TTA)3Bipy through a sol-gel method and embedding it into a composite matrix composed of aluminum oxide and polyvinyl alcohol. Example

[0047] A highly weather-resistant warning sign material for ship decks, which differs from Example 1 in that the raw material encapsulated rare earth in the polyester adhesive layer is prepared by dispersing Eu(TTA)3Bipy through a sol-gel method and embedding it into a composite matrix composed of zinc oxide and polyvinyl alcohol.

[0048] Comparative Example 1 A warning sign material, which is different from Example 1 in that the raw material acrylate resin in the polyester adhesive layer is epoxy acrylate resin selected from Tianmen Hengchang Chemical HC0270.

[0049] Comparative Example 2 A warning sign material, which is different from Example 1 in that stainless steel foil is used to replace the forged aluminum foil to form a stainless steel foil layer.

[0050] Performance Testing 1. Weather resistance test: The highly weather-resistant warning sign material for ship decks prepared in the embodiment of the present application and the warning sign material prepared in comparative example 1-2 were subjected to a weather resistance test; the test method is as follows: The test samples were directly exposed to strong light simulation, water immersion simulation and salt spray simulation conditions in a sunny exposure test field in Florida, USA for 6 months. Evaluation indicators: observe and record the color change, cracking, gloss change and other appearance changes of the samples.

[0051] The test results are shown in the table below:

[0052] By analyzing the data in the above table, the highly weather-resistant warning sign materials for ship decks prepared in Examples 1-11 performed excellently in the weather resistance test, with no cracking and no significant changes in color and glossiness; In Examples 12 to 14, the weather resistance test results for the highly weather-resistant warning sign material for ship decks showed a clear downward trend; Specifically, Example 12 showed slight cracking and gloss loss, Example 13 showed slight fading and gloss loss, and Example 14 suffered from slight fading, cracking and serious gloss loss at the same time. This series of phenomena strongly suggests that the matrix material of the encapsulated rare earth has a significant impact on the weather resistance of the final product. Among them, the combination of aluminum oxide and polyacrylic acid (as shown in Example 1) stood out in the weather resistance test due to its excellent stability and anti-aging performance, becoming the best performing material combination. In contrast, when the matrix material is replaced with zinc oxide or polyvinyl alcohol, the weather resistance of the product declines, which is specifically manifested in the increase of negative phenomena such as cracking, fading and gloss loss.

[0053] The performance of the products in Comparative Examples 1 and 2 further confirms the key role of material selection in product performance. The epoxy acrylate resin used in Comparative Example 1 is obviously inferior to the original acrylate resin in terms of weather resistance, especially UV resistance, resulting in serious fading, cracking and slight gloss loss in the product. In addition, the epoxy acrylate resin also shows poor compatibility with other material layers (such as substrates and pigment layers), further accelerating the reduction of gloss during the aging process.

[0054] In Comparative Example 2, although stainless steel foil is favored for its excellent corrosion resistance and durability, it cannot completely avoid slight fading under specific environmental conditions such as long-term ultraviolet radiation. The bonding strength between the stainless steel foil and the substrate or other composite material layers may be insufficient. This lack of bonding strength is particularly obvious on surfaces such as decks that are frequently subjected to stress and slight deformations, which can easily lead to serious cracking problems. This phenomenon is partly attributed to the relatively low flexibility and ductility of stainless steel foil, which makes it difficult to fully adapt to the slight deformation of the deck surface caused by environmental factors (such as temperature fluctuations and humidity changes). Ultimately, these cracks not only damage the overall integrity of the material, but also aggravate the gloss loss effect due to the uneven surface, further affecting the visual effect and durability of the warning sign material.

[0055] 2. Anti-slip test: According to DIN 51130 Tests on floor coverings. Determination of anti-slip properties. Workrooms and work areas with risk of slipping and falling. Trampling method. Slope test method, test the anti-slip properties and record the test results in grades.

[0056] The test results are shown in the table below:

[0057] By analyzing the data in the above table, the anti-skid grade of the highly weather-resistant warning sign material for ship decks prepared in Example 1 reaches the highest grade R13, while the anti-skid grades in Examples 2-13 are between R10-R11, and the anti-skid grade of Example 14 is R9; As for Comparative Example 1 and Comparative Example 2, the anti-slip levels are R10 and R12, respectively.

[0058] The specific material combination and preparation process used in Example 1 enable its anti-slip grade to reach the highest grade R13. This is mainly due to the effective dispersion and fixation of the encapsulated rare earth by the composite matrix composed of aluminum oxide and polyacrylic acid, as well as the precise proportion and good compatibility of the components in the polyester adhesive layer (such as acrylic resin, ethyl acetate, etc.). This optimized combination not only improves the overall performance of the material, but also significantly enhances its anti-slip properties.

[0059] In contrast, although the raw materials of the polyester adhesive layer were slightly adjusted in Examples 2 to 13, the anti-slip grades did not reach the level of Example 1, but remained between R10 and R11. This shows that although these adjustments may have affected certain properties of the material (such as weather resistance, glossiness, etc.) to a certain extent, they did not significantly improve the anti-slip performance, especially in Example 14, whose anti-slip grade dropped to R9, which may be due to the poor effect of the composite matrix composed of zinc oxide and polyvinyl alcohol in dispersing the encapsulated rare earth, or poor compatibility with other components in the polyester adhesive layer.

[0060] As for Comparative Examples 1 and 2, the anti-slip grades are R10 and R12, respectively, which are lower than Example 1 but higher than some examples. In Comparative Example 1, epoxy acrylate resin is used instead of acrylate resin, which may affect the overall performance of the polyester adhesive layer, including the adhesion, hardness, elasticity, etc. with the aluminum foil layer and the bottom layer, thereby affecting the anti-slip performance. Although stainless steel foil is used instead of forged aluminum foil in Comparative Example 2, the anti-slip performance does not change much.

[0061] 3. Luminous afterglow performance test: Use a fluorescent lamp with a color temperature of (6500±500)K as the excitation light source, and fully irradiate the test sample under the specified illumination conditions. Then move the sample to a dark room, observe and record its luminescence in a dark environment, and evaluate the indicator: measure the duration of the sample's luminous afterglow.

[0062] The test results are shown in the table below:

[0063] Through the data analysis of the above table, we can observe that the highly weather-resistant warning sign materials for ship decks prepared from Examples 1 to 14 and Comparative Examples 1 and 2 all exhibited good performance in the luminous afterglow performance test, and the duration of the luminous afterglow was maintained between 6.6 and 9.8 hours. Within this range, Example 1 has the longest duration of luminous afterglow and performs the best, so it can be regarded as a preferred example; However, it is worth noting that compared with Example 1, the high weather-resistant warning sign materials for ship decks prepared in Examples 12 to 14 have a large performance gap in luminous afterglow performance, which may be due to the following aspects: Differences in composite matrices of encapsulated rare earths: In Examples 12 to 14, the composite matrices of encapsulated rare earths respectively used a combination of zinc oxide and polyacrylic acid, aluminum oxide and polyvinyl alcohol, and zinc oxide and polyvinyl alcohol. These different matrices may affect the dispersion effect and stability of the rare earth elements and the interaction with other components in the polyester adhesive layer, thereby affecting the luminous properties of the material and the duration of the luminous afterglow.

[0064] Compatibility of the matrix and the polyester adhesive layer: Different composite matrices may have different compatibility with the polyester adhesive layer. If the compatibility is poor, it may lead to uneven dispersion of the matrix in the polyester adhesive layer, or shedding and migration during use, thus affecting the overall performance of the material and the luminous afterglow effect.

[0065] In summary, the reason why the high weather-resistant warning sign material for ship decks can show excellent performance in weather resistance, anti-slip performance and luminous afterglow performance is mainly due to the combined effect of the following key factors: Careful selection of matrix materials: The luminous body composite matrix composed of aluminum oxide and polyacrylic acid provides a solid foundation for the entire material system with its excellent chemical stability and physical properties. This matrix not only enhances the overall strength of the material, but also promotes the uniform dispersion and close combination of each component, thereby improving the overall performance of the material; Scientific ratio of high-performance materials: The precise addition of high-performance materials such as acrylic resin, ethyl acetate and encapsulated rare earth (such as Eu(DBM)3Phen, Eu(TTA)3Bipy and other rare earth europium complexes) in the specially formulated polyester adhesive layer not only significantly improves the weather resistance of the material, enabling it to maintain bright colors for a long time in harsh marine environments and not easily fade or age, but also optimizes the luminous performance to enhance visibility at night or in low-light environments; Strict control of the preparation process: During the preparation process, the solid content, viscosity and monomer raw material ratio of the acrylic resin are carefully controlled to ensure the excellent fluidity and molding ability of the resin, reduce bubbles and defects during the processing, and at the same time, the leveling agent and mineral oil defoamer added during the preparation of the polyester adhesive layer further improve the surface quality of the coating, and enhance the uniformity and adhesion of the coating; Guarantee of compatibility and stability: The good compatibility between the components enables the entire material system to remain stable during processing and use, avoiding performance degradation or failure due to material incompatibility. The encapsulated rare earth is evenly dispersed and embedded into the composite matrix through the sol-gel method, which not only improves the stability of the rare earth elements, but also optimizes their luminescence properties.

[0066] The above are all modifications without creative contribution or solutions that obviously constitute technical inspiration that can be made to the present embodiment as needed by technical personnel in this field after reading this specification, but they should be protected by patent law as long as they are within the scope of the claims of this application.

Claims

1. A highly weather-resistant warning sign material for ship decks, characterized in that: The invention comprises an aluminum foil layer and a bottom layer, wherein the aluminum foil layer is composed of forged aluminum foil, and the bottom layer is composed of environmentally friendly isolation paper; the aluminum foil layer and the bottom layer are bonded by a polyester adhesive layer, wherein the raw materials for preparing the polyester adhesive layer, by weight percentage, include: Acrylate resin 28-30% Ethyl acetate 44-48% Encapsulated rare earth 10-15% Flame retardant 3-4% Leveling agent 1-3% Anti-aging agent 1-3% Mineral oil defoamer 1-2% Wherein, the acrylate resin is prepared from acrylic acid monomer, vinyl triethoxysilane monomer and glycidyl methacrylate, and its specific preparation method includes: S1, uniformly mix acrylic acid monomer and vinyl triethoxysilane monomer, place them in a reaction container, add solvent and initiator, raise the temperature to 75-105° C. and keep the temperature for reaction for 1-1.5 hours to obtain mixture A; S2. Add glycidyl methacrylate to the mixture A after the reaction in S1, then raise the temperature to 140-155° C. and keep the mixture to react for 2.5-3 hours, and then obtain the acrylic resin after post-treatment.

2. The highly weather-resistant warning marking material for ship decks according to claim 1, characterized in that: The solid content of the acrylic resin is 52-55%, and the viscosity is 1250-2500 mPa·s.

3. The highly weather-resistant warning marking material for ship decks according to claim 1, characterized in that: In the preparation step of the acrylic resin, the feeding amounts of acrylic acid monomer, vinyl triethoxysilane monomer and glycidyl methacrylate are calculated by weight ratio, and acrylic acid:vinyl triethoxysilane:glycidyl methacrylate is 1:(0.04-0.06):(0.01-0.02).

4. The highly weather-resistant warning marking material for ship decks according to claim 1, characterized in that: In the preparation step of the acrylic resin, the feeding amounts of acrylic acid monomer, vinyl triethoxysilane monomer and glycidyl methacrylate are calculated by weight ratio, and acrylic acid:vinyl triethoxysilane:glycidyl methacrylate is 1:(0.044-0.051):(0.014-0.018).

5. The highly weather-resistant warning marking material for ship decks according to claim 1, characterized in that: The encapsulated rare earth is prepared by dispersing a rare earth europium complex through a sol-gel method and embedding the complex into an encapsulating matrix.

6. The highly weather-resistant warning marking material for ship decks according to claim 5, characterized in that: The rare earth europium complex is selected from Eu(DBM)3Phen, Eu(TTA)3Bipy, Eu(TTA)3phen or Tb(TTA)3Bipy.

7. The highly weather-resistant warning marking material for ship decks according to claim 5, characterized in that: The encapsulating matrix is ​​a composite matrix composed of aluminum oxide and polyacrylic acid.

8. The method for preparing the highly weather-resistant warning marking material for ship decks according to any one of claims 1 to 7, characterized in that: The following steps are involved: A1. Preparation of polyester glue: Add acrylate resin, then add ethyl acetate, encapsulated rare earth, flame retardant, leveling agent, antioxidant and mineral oil defoamer in a reaction vessel, raise the temperature to 95-110° C., keep the temperature for reaction for 2.5-3 hours, and obtain polyester glue; A2. Assembly: Prepare forged aluminum foil and environmentally friendly isolation paper, then coat the surface of the forged aluminum foil with the polyester glue prepared by A1 after surface pretreatment, with a coating thickness of 5-6U, and then attach the environmentally friendly isolation paper, and after curing, form an aluminum foil layer and a bottom layer to obtain a highly weather-resistant warning sign material for ship decks.